RANCANGAN SISTEM PENGISIAN TANGKI UTAMA BAHAM BAKAR GENSET DARI TANGKI CADANGAN MENGGUNAKAN ARDUINO DI BANDAR UDARA INTERNASIONAL JUWATA - Irvan Imansyah; Zulina Kurniawati; Agus Herianto (Politeknik Penerbangan Indonesia Curug, 2017)
At Juwata International Airport, there are frequent blackouts by PLN. This causes the generator as backup power supply is often used, which makes refueling so often done. The current refueling is still manual using pump or filled directly from Pertamina‟s tanker. When doing manual refueling ever happened error, that spill of fuel.To know the fuel capacity from primary and secondary tank is currently still using the indicator hose from the height of fuel in tank. The fuel capacity in tank must always be checked to support the fuel needs of generator if PLN do the blackouts.This design use arduino as central control of system to be created. In addition this design also consists of ultrasonic sensors to know the fuel volume, relays as pump control, LED as indicator of filling mode and buzzer as warning to technician if the fuel volume reached the bottom level. This design us expected to help technician duty when refueling or fuel capacity check and can be solution of the exsisting problem.